A revision of Amarochara of the Holarctic region. III. A new species, a new synonym, and additional records (Coleoptera, Staphylinidae: Aleocharinae) - Assing, Volker (Zootaxa, 2007)
Amarochara formicina sp. n. (Canada: New Brunswick), the 26th representative of the genus in the Holarctic region, is described and illustrated. The following synonymy and new combination are proposed: Amarochara freyi (Bernhauer, 1940), comb. n. (ex Ocyusa) = Amarochara splendens Jarrige, 1952, syn. n. Additional records are reported for several species of the Palaearctic and Nearctic regions. The previously unknown aedeagus of A. inquilina (Casey, 1906) is illustrated.